2022
DOI: 10.1007/s11356-022-23238-8
|View full text |Cite
|
Sign up to set email alerts
|

Waste management and green technology: future trends in circular economy leading towards environmental sustainability

Abstract: The effective treatment of waste to be used as a resource in future has a major role in achieving environmental sustainability and moving towards circular economy. The current research is aimed to provide in-depth detail regarding prominent trends and research themes, evolution, future research orientation, main characteristics, and mapping of research publications on waste management, technological innovation in circular economy domain from the year 2000 to 2021. Different analyses including text mining and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 215 publications
1
20
0
1
Order By: Relevance
“…Several factors, such as environmental knowledge upgrading programs, can be implemented at the individual, community, and societal levels to elevate social values ( 91 , 92 ). Social media can increase knowledge at the individual level by delivering broadcasts or adverts directly to each user.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, such as environmental knowledge upgrading programs, can be implemented at the individual, community, and societal levels to elevate social values ( 91 , 92 ). Social media can increase knowledge at the individual level by delivering broadcasts or adverts directly to each user.…”
Section: Discussionmentioning
confidence: 99%
“…Tzanakakis et.al [45] reported that according to the findings of an OECD survey on the circular economy in regions and cities, 66% of the surveyed circular economy initiatives discovered water and sanitation as crucial sectors for circular economy application, closely followed by the waste sector (78%). In addition, the effective treatment of waste to be used as a resource in the future is critical to achieving environmental sustainability and moving toward a circular economy [50].…”
Section: Circular Economy In the Context Of Energy And Water Sectorsmentioning
confidence: 99%
“…Environmental pollution and sustainable development have become an increasingly important issue [13,14]. The economic effects of environmental regulation are widely concerned and studied.…”
Section: Research On Environmental Regulationmentioning
confidence: 99%